Adverts and Spam in E-Commerce: Improving Confidence - A. R. Valamat-Zade; M. G. Girich; A. D. Levashenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article analyzes global and Russian market of e-advertising and trends in its development. E-commerce market in Russia can grow to 3.491 trillion rubles by the end 2023. The increase in on-line purchase frequency and number of buyers takes place due to effective on-line marketing, whose expenses in 2017 exceeded expenses on TV commercials. In Russia there are no rules (and restrictions) concerning on-line adverts placement. It could lead to the fact that the number of adverts surpasses the volume of meaningful information. The notion of on-line advertising in the Russian Federation is limited by the general idea of advertisement, while in many countries its specific definition is put forward in order to provide an opportunity to advance special requirement to it. One problem of on-line advertising is a great amount of spam interfering both with the customer and business-communities as a result of dropping confidence of buyers. Russia is included in five most active span distributors. Today spam makes over 60% of all incoming correspondence in public mail services of the Russian segment of the Internet. The authors propose to upgrade Russian legislation and direct it to spam regulation, which could protect customers’ rights and raise their confidence to e-commerce and to development and adoption of special guiding principles that would explain ways of using laws concerning adverts in the Internet.